Di-?-iodo-bis[dicarbonylrhodium(I)] - Burger, Sylvain; Therrien, Bruno; Süss-Fink, Georg (My University, 2003)
Crystals of the title complex are monoclinic, space group P21/n, with a 9.4160(13), b 9.589(1), c 11.3024(16) Å. ? 96.091(17)°; Z = 4, dc = 3.742; R = 0.053, Rw(F2) = 0.141 for 1980 reflections. The dinuclear complex adopts a V-shape conformation with an intramol. Rh...Rh distance of 3.385(1) Å. The mols. are connected in a zigzag fashion, with intermol. Rh...Rh distances of 3.637(2) Å. [on SciFinder(R)]
Keywords: crystal structure rhodium carbonyl iodo; mol structure rhodium carbonyl iodo